Improving timeliness of hepatitis B vaccine administration in an urban safety net level III NICU. Issue 11 (17th May 2021) - Hayashi, Madoka; Grover, Theresa R; Small, Steve; Staples, Tessa; Roosevelt, Genie
Abstract : Objective: To avoid preventable consequences of perinatal hepatitis B infection, all infants should be given hepatitis B vaccine (HBV) within 24 hours of birth if birth weight is ≥2 kg and at 30 days of life or at discharge if <2 kg, to provide highest seroprotection rates while ensuring universal vaccination prior to discharge. We aimed to achieve timely HBV administration in >80% of eligible infants in both birthweight groups and decrease infants discharged home without receiving HBV to <1% over an 18-month period and sustain results for an additional 15 months. Methods: Data were collected from June 2016 to May 2020 in a level III neonatal intensive care unit. A multidisciplinary team identified barriers and interventions through Plan-Do-Study-Act cycles from September 2017 to February 2019: using pharmacists as champions, overcoming legal barriers, staff education and best practice alerts (BPAs) embedded in electronic health records. Statistical process control (SPC) p charts were used to evaluate the primary outcome measure, monthly percentage of infants receiving timely HBV administration stratified by birthweight categories (≥2 and <2 kg). For infants receiving HBV outside the time frame, absolute difference of timeliness was calculated. Results: Mean timely HBV administration improved from 45% to 95% (≥2 kg) and from 45% to 85% (<2 kg) with special cause variation in SPC charts. Infants discharged without receiving HBV decreased from 4.6% to 0.22%. Of those given HBV outside the recommended time frame, median absolute time between recommended and actual administration time decreased significantly: from 3.5 days (IQR 1.6, 8.6) to 0.3 day (IQR 0.1, 0.8) (p<0.001) in ≥2 kg group and from 6 days (IQR 1, 15) to 1 day (IQR 1, 6.5) (p=0.009) in <2 kg group. Conclusions: Using a multidisciplinary approach, we significantly improved and sustained timely HBV administration and nearly eliminated infants discharged home without receiving HBV. Pharmacists as champions and BPAs were critical to our success.